Linguagem e identidade de pescadores do Lago de Itaipu - Butzge, Clovis Alencar (2006)
The present work consist of a study of ethnographic sociolinguistic case about the relations between language and identity at the community of fishermen training in Santa Helena City, Paraná State, Brazil, which they act at Lake Itaipu, formed in 1982 from the construction of hydro-electric power station of Itaipu Binacional on, between the Federal Republic of Brazil and Republic of Paraguay. The corpus of this research is composed of recorded interviews among 2003 and 2005, which speak about life history of fishermen and fisherwomen, collected from visits field on taken place through the project of research Trajectories social and border work: study of the case of fishermen in Santa Helena/PR , linked with the Center of Humanities, Education and Languages of Unioeste, Marechal Cândido Rondon, Campus. To contextualize the interviews it was realized a description of the context partner-historicalgeographical at the community of professional fishermen of Santa Helena, apart from contextualization of the visits field. The narratives are deal with as speeches, from which the subject reveal and act, building symbolically representation of one and the world, realizing through the language one process of identification. It is established that the community of professional fishermen is recent that is why most of the members are still building their representation about the fishing activities as well as the identification with the fishing professional. Therefore, it started from perspective of the subject at the narrative to delineate a profile of the identity social of fishermen and not from an outside feeling; it can also establish that it is already in progress the formation of a profile of not-fisherman, proving by reasoning that the process of differentiation is fundamental at the constitution of identities. It establishes a strong process of decentralization at the identity of the interviewees about fishing, special for being resulting from other professions or even for having a parallel profession to the fishing. Despite of the complexity and heterogeneity, many points in common were founded at the speeches of the interviewees, revealing that is in operation the building of a representation collective of the identity social of fisherman among fishermen. It also gave attention to aspects lexical and phonological of the fishermen language, what came to the conclusion that it is in formation a sociolect of the fishing. It was realized a survey of vocabulary used at the fishing universe, which besides designate rudiments that consist the environment, the tools, the practice of fishing, and the organization fishing, still reveal the elements of culture, quotidian, relations social at the community of fishermen. It is also realized an analysis to check if there is an understanding through the fishermen of prejudice about the profession they perform, concluding that besides the prejudice against the profession, there is a prejudice about language and about the intellectual formation of the fishermen, resulting in a process of stigmatization of their profession, what make most of the fishermen not to want to transmit to their kids. Thus, despite of the complexity and the plurality identity verified, intrinsic relation between language and identity allowed noticing, trough the analysis of the narratives how it is being building and how the identity social of fishermen of the Lake Itaipu consists.